As privatizações no primeiro governo Fernando Henrique Cardoso nos editoriais da Revista Veja (1995-1998) - Karling, Ademir Vilson (2019)
The central objective of this research is to analyze how they were treated in the editorials of Veja magazine privatizations in the first Fernando Henrique Cardoso government (1995-1998), verifying the positioning of this press vehicle. To this end, we will analyze 205 editions, corresponding to the number 1373 from January 4th of 1995 to number 1578 of December 23rd of the year 1998. As secondary objectives we will seek to study how the privatization processes of first FHC government. Also understand how the political and economic context of that period influenced the privatization process and verify the role played by the Veja Magazine on the political and economic debate in the First FHC Government. The present work proposes, therefore, to carry out an analysis of the representation of these privatizations in the Fernando government Henrique Cardoso in his first term (1995-1998) using Veja magazine as his source. For such, We will analyze how the topic was treated in the magazine's editorials and what position it deserved.